Analysis of Mental Health Care Services in Child Care Institutions - Saluja, Khushi (Trinity Law Review, 2023)
For several months, mental healthcare has been the talk of the town. Children particularly in child care institutions need a well-structured plan for their welfare services made with the help of mental health experts. Studying the stages of a kid’s mental growth and improvement enables one to better prepare for what is ahead and support the child as they grow and develop with. Certain institutions have expressed concerns over the detrimental effects of traditional assessment strategies, particularly institutionalized paper-and-pencil evaluations for various decision and accomplishments. There is growing consensus that any changes to educational programmes must also involve adjustments to assessment. Under certain areas, growing up in today’s society is much harder than it was in earlier decades. A growing and challenging educational system is something that many youngsters deal with. According to the statistics, 75% of children in childcare centres who experience mental health problems aren’t getting the help they need. Physical and mental development are extremely essential. Adults may find it challenging to recognise when a kid requires assistance with mental health difficulties. Childcare Centres should take appropriate actions to support children in getting the help they need. Additionally, it might be challenging for young people to speak out about the difficulties they are having but they can be improvised by programs headed by mental health experts. This study further considers the analytical function and duties of various stakeholders in the child care and protection system within the domain of mental health care.
Keywords: Mental health; child care